THE MUSICAL CONCEPT OF OGUANG JANA IN PARAMBAHAN VILLAGE - Indra Ariffin (LPPM Institut Seni Indonesia Padangpanjang, 2023)
Oguang jana is a type of bronze musical ensemble found in Nagari Parambahan, Lima Kaum sub-district, Tanah Datar district. This art is played by four players, each player holding a canang musical instrument (a type of gong family one level larger than the talempong). This art is commonly carried out in various traditional events and other community entertainment. This study intends to examine the musical concepts that exist in the art of oguang. In addition, studies outside of music texts will also be put forward by the author as an effort to get to know this art beyond the resulting musical texts. Research on this object is also based on the urgency of this art. Where this art no longer has a successor and is very rarely presented in various art stages. Therefore, this research is very important for the author. This research uses qualitative methods to describe things related to the text and context of this art.